A heuristic algorithm for container loading of pallets with infill boxes - Sheng, Liu; Hongxia, Zhao; Xisong, Dong; Changjian, Cheng (European journal of operational research, 2016)
•The algorithm is suitable for container loading of pallets with infill boxes.•The algorithm satisfies the single support constraint on pallets.•The algorithm achieves competitive results for BR1–BR15. We consider the container loading problem that occurs at many furniture factories where product boxes are arranged on product pallets and the product pallets are arranged in a container for shipments. The volume of products in the container should be maximized, and the bottom of each pallet must be fully supported by the container floor or by the top of a single pallet to simplify the unloading process. To improve the filling rate of the container, the narrow spaces at the tops and sides of the pallets in the container should be filled with product boxes. However, it must be ensured that all of the infill product boxes can be entirely palletized into complete pallets after being shipped to the destination. To solve this problem, we propose a heuristic algorithm consisting of a tree search sub-algorithm and a greedy sub-algorithm. The tree search sub-algorithm is employed to arrange the pallets in the container. Then, the greedy sub-algorithm is applied to fill the narrow spaces with product boxes. The computational results on BR1–BR15 show that our algorithm is competitive.